Influence of storage time on the flavor and texture of egg yolk gel - Tingting Tang; Mingsheng Xu; Yanjun Yang (Food Chemistry: X)
The physicochemical properties, structure, and flavor of yolk gels stored under 4 °C conditions were investigated using GC–MS, electronic nose analysis, and texture profiling, provided valuable insights into determining the optimal processing time for egg yolks. During storage, the hardness increased significantly from 3649.50 g to 5129.75 g, while its elasticity decreased from 0.92 to 0.78. Changes in the secondary and tertiary structures of egg yolk were characterized by ultraviolet and infrared spectroscopy. Furthermore, the spatial conformation of yolk proteins altered during storage, leading to increased exposure of charged groups, -SH groups, and hydrophobic regions. These exposed functional groups interacted with flavor compounds, enhancing their binding affinity, hexanal, heptanal, 2-pentyl-furan, octanal and dimethyl trisulfide were reduced. The results demonstrated that as storage time extended, the overall flavor intensity of egg yolk hot gels diminished. Consequently, based on specific requirements, it is possible to select egg yolks processed at corresponding storage durations.